Kant on thinking for oneself and with others—the ethical a priori, openness and diversity. Issue 6 (3rd December 2021) - Sticker, Martin
Abstract: Immanuel Kant famously wants us to think for ourselves. However, thinking collaboratively is often preferable to solitary thinking, especially in educational contexts. In this paper, I argue that Kant does not advocate a problematic form of epistemic or pedagogical individualism. For my argument, I focus on the area that, one might suspect, lends itself the least to collaborative reasoning on Kant's framework: morality founded in rational a priori structures. I show that Kant is aware of both the prospects and limits of reasoning on one's own and with others. According to Kant, openness, rooted in an attitude of mutual trust, is required to reason well with others. Kant, however, does underestimate the significance of diversity for collaborative reasoning.